Alleviating debt distress and advancing the sustainable development goals. (3rd May 2021) - Haughton, Howard; Keane, Jodie
Abstract: External debt levels will be unprecedented in 2021—in this last decade of action to secure the sustainable development goals (SDGs)—and mostly in distress for low‐income‐developing countries (LIDC) and least developed countries (LDCs). However, increased levels of debt distress were on the horizon even before the dire economic effects of COVID‐19. These high levels of external debt and a decreasing inability to access international capital were already expected to impede the advancement of the SDGs; the situation has become far graver because of the Great Lockdown and efforts to stymie transmission of COVID‐19. The international community faces perhaps its greatest challenge: it must alleviate poor countries debt burdens exacerbated by COVID‐19 to effectively combat its spread, but there is no consensus as to how to achieve this. Though there is no historical parallel to the current debt crisis, the heavily indebted poor country initiative (HIPC) suggests debt relief alone will be insufficient to keep the SDGs on track. While the challenges that arise with regards to the scaling up of debt swap initiatives—learned from previous efforts—are formidable, this article provides critical reflection as to their effective operationalization within the current context: responding to the economic and social devastation wrought by COVID‐19 and keeping the SDGs on track. It shows how debt swaps can be effectively deployed as part of a revitalized global partnership for development, for the advancement of the SDGs and broader debt sustainability.